PEMBANGUNAN BERKELANJUTAN DALAM PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP DALAM KERANGKA OTONOMI DAERAH - Zunnuraeni -; Kafrawi -; Abdul Khair (Faculty of Law, University of Mataram, 2017)
This research aims to know the obligation and authority of regional government in integrated sustainable development in a region environment matter. This research is a normative research with statatute approach and conceptual approach.The data gathered by library research and then analyzed with qualitative method. Result of this research showed that to meet the obligation to integrated sustainable development in regional affair the regional government must arranged Planning of Environment Protection and Management (PEPM/RPPLH) and Strategic Environment Analysis (SEA/KLHS). Authority of regional government to exploit natural resources shall through a planning phase by means of PEPM. Likewise with all the policy, planning and program that potentially caused impact or risk to environment shall have SEA first. PEPM and SEA must included in The Regional Midlle Term Planning and The RegionalLong Term Planning (RPJMD and RPJPD)